Analysis of the Needs for Developing MI/SD Science Learning Design Based on Local Wisdom - Daluti Delimanugari; Na'imah; Suyadi; Fitrotunisa, Ana; Amin, Lailla Hidayatul; Sari, Rita (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to develop a science learning design based on local wisdom in MI/SD Gunungkidul by utilising the uniqueness of local culture and natural resource wealth, such as traditional agricultural practices, natural resource management, and local community lifestyles. This research uses a qualitative approach involving 17 teachers as the main source to obtain in-depth data about their experiences, challenges, and needs in implementing local wisdom-based learning. With semi-structured interview instruments and data analysis through three stages data reduction, data presentation, and conclusion, the study is guided by three problem formulations: (1) how local wisdom-based science learning is implemented in schools, (2) why such a design is important in Gunungkidul, and (3) what its impacts are. These problems directly align with the research objectives, which are to explore current implementation practices, analyse the urgency and contextual relevance of integrating local wisdom into science education, and evaluate its potential impact on science literacy, cultural and environmental preservation, and student creativity. The findings show varying levels of implementation, with some schools beginning integration despite challenges such as limited facilities and teacher readiness. Overall, the local wisdom-based science learning approach makes lessons more meaningful and relevant to students' lives.